CHARACTERISTIC OF SUICIDE VICTIMS BEFORE, DURING, AND AFTER COVID-19 PANDEMIC IN PROF. DR. I. G. N. G. NGOERAH GENERAL HOSPITAL - Nibbana Siva (Fakultas Kedokteran Universitas Jenderal Soedirman, 2026)
Suicide is a mental health issue that requires more attention. The COVID-19 pandemic has brought significant changes in various aspects, including mental health, which may influence the characteristics of suicide victims. This study aims to identify the characteristics of suicide victims before, during, and after the COVID-19 pandemic at Prof. dr. I. G. N. G. Ngoerah General Hospital. This is a descriptive study with a retrospective cross-sectional design using data from external post-mortem examination reports from December 11, 2016, to December 31, 2024. Data meeting the inclusion and exclusion criteria comprised 188 cases, including 59 cases before the pandemic, 90 cases during the pandemic, and 39 cases after the pandemic. The results showed an increase in the number of suicide cases during the pandemic compared to before the pandemic, with a predominance of characteristics in the adult age group, males, and Indonesian citizens. The conclusion of this study is that the COVID-19 pandemic contributed to an increase in suicide rates and the characteristics of the victims. Keywords: suicide, COVID-19 pandemic, victim characteristic